1998
DOI: 10.1046/j.1469-0705.1998.11020141.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis and perinatal management of a lingual lymphangioma

Abstract: We describe the prenatal ultrasonographic features that led to the diagnosis of a lingual lymphangioma. The risk of upper airway obstruction, which is associated with this rare abnormality, prompted us to plan careful perinatal management. We believe that, in cases of suspected lymphangioma of the tongue or other oropharyngeal tumors, elective delivery should be carried out in a tertiary referral center in which emergency ventilation and tracheostomy are possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…The sonographic characteristics of this case are similar to previously published cases of axillary, neck and lower extremity lymphangiomas [9,23,[30][31][32]. More recently, Paladini et al [21] reported on the untypical localization of a lingual lymphangioma. In 1998 Suzuki et al [32] presented a series of 24 cases of cystic lymphangiomas.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The sonographic characteristics of this case are similar to previously published cases of axillary, neck and lower extremity lymphangiomas [9,23,[30][31][32]. More recently, Paladini et al [21] reported on the untypical localization of a lingual lymphangioma. In 1998 Suzuki et al [32] presented a series of 24 cases of cystic lymphangiomas.…”
Section: Discussionsupporting
confidence: 86%
“…In previous reports fetal lymphangiomas have been described in various locations [6,21,[30][31][32]. The sonographic characteristics of this case are similar to previously published cases of axillary, neck and lower extremity lymphangiomas [9,23,[30][31][32].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The prevalent sites are the head and neck region 8,9) , however, lymphangioma rarely affects the oral cavity. Antenatal diagnosis is sometimes possible through ultrasonography 10) . Lymphangioma is the most common cause of secondary macroglossia in infancy.…”
Section: Discussionmentioning
confidence: 99%
“…A case of lingual lymphangioma has been reported by Paladin and coworkers. 8 A large congenital oropharyngeal tumor may cause partial to complete obstruction of the fetal mouth, thus leading to polyhydramnios in late pregnancy. After birth, acute airway obstruction and feeding problems may be encountered.…”
Section: Discussionmentioning
confidence: 99%